HUBUNGAN AIR TERKANDUNG DENGAN REFLEKTIFITAS RADAR - Eddy Hermawan; Yuanita Handayati (Lembaga Penerbangan dan Antariksa Nasional, 2007)
This paper is mainly concentrated to the correlation between Total Precipitable Water (TPW) on one single column of the vertical air mass and radar reflectivity (Z) over Kototabang (0.2˚S; 100.32˚E), Bukittinggi, West Sumatera based on to the analysis of Radio Acoustic Sounding System (RASS) and Boundary Layer Radar (BLR) data during the Coupling Processes of Equatorial Atmosphere (CPEA) Campaign I from April 10 to May 9, 2004 was going on. wWe firstly reviewed yhe basic concept of TPW using the Weisner method ti estimate the TPW value from the radiosonde data. We reviewed the basic concpt of RASS and BLR system also, especially on the Z data analysis. By arranging the mean value of RASS data every 10 minutes and 150 meter in height, respectively, we estimated the TPW values from the RASS data. By analysing the Cross Cirrelation Function (CCF) of both values taken from SPSS software version 13, we found a good agreement between TPW and Z parameter, especially on 5 May 2004. The correlation values are 0.05, and 0.61 at around 2.7 and 2.25 km, repectively. Although, the maximum correlation value in only 0.61, but this is still good enough to describe the correlation between TPW and Z.